Rehabilitation Technical Operation Standard of Traditional Chinese Medicinefor Moxibustion with Seed-sized Moxa-cone - Working Group of Rehabilitation Technical Operation Standard of Traditional Chinese Medicine for Moxibustion with Seed-sized Moxa-cone (康复学报)
Moxibustion with seed-sized moxa-cone belongs to the category of direct moxibustion in moxibustion therapy, which is a kind of therapy to prevent and treat diseases by directly burning the moxa cone in the size of wheat grain on the acupoints and stimulating the acupoints of the body with the help of moxibustion fire and drugs. Wheat grain moxibustion has the effects of supporting righteousness and expelling evil, warming meridians and dispersing cold, promoting blood circulation and relieving pain, tonifying middle-Jiao and supplementing Qi, disease prevention and health care, etc. It has been widely used in the treatment of a variety of clinical diseases and health care. The main purpose of formulating the operation specification of traditional Chinese medicine rehabilitation technology of wheat grain moxibustion is to standardize the management and guide the professional and technical personnel of traditional Chinese medicine to correctly use wheat grain moxibustion therapy. This standard focuses on the preparation before moxibustion (preparation of moxibustion cone for wheat grain moxibustion, acupoint selection and positioning, body position selection, other auxiliary supplies, patient preparation, environmental health requirements, disinfection) by formulating standards on the technical scope of wheat grain moxibustion, normative references, terms and definitions, operation steps and requirements, precautions, taboos, appendices, references, etc. The operation steps and requirements of moxibustion (moxibustion principle, operation steps of suppurative wheat grain moxibustion, operation steps of non suppurative wheat grain moxibustion), post-treatment of moxibustion and other operation steps shall be standardized. In addition, the preparation of moxa cone with wheat grain moxibustion, reinforcing and reducing techniques, the main functions and indications of wheat grain moxibustion rehabilitation technology are also standardized. This technical specification is applicable to traditional Chinese medicine professionals and technicians in hospitals at all levels and medical and health care institutions, and has good applicability and effectiveness.